AN ANALYSIS OF PROTEIN AND CALORIE CONSUMPTION IN CENTRAL JAVA - Agus Widarjono (Economic Journal of Emerging Markets, 2014)
Abstract This study analyses calorie and protein consumption in Central Java Province. The calorie and protein elasticity are derived from demand elasticity of the ten food groups encompassing cereals, fish, meats, eggs and milk, vegetables, fruits, oil and fats, prepared foods and drinks, other foods and tobacco products. Most of calorie and protein-price elasticity of the ten food group are negative. Consumption of calorie and protein are most responsive to prices of eggs and milk. Protein -price elasticities are less elastic than calorie-price elasticities. Calorie and protein-income elasticity are positive and become lesselastic in moving from lower to higher income households but protein is less responsive to income change than calorie. Keywords: QUAIDS, demand elasticity, nutrient elasticity, Central Java ProvinceJEL Classification numbers: D12, O12